A location-based multi-factor authentication scheme for mobile devices. (22nd August 2022) - Meher, Bimal Kumar; Amin, Ruhul
In this paper, we propose a robust and user-friendly multi-factor authentication scheme without using smart card to reduce the operational overhead and hardware cost incurred due to the card reader. It also eliminates the issues when the smart card is lost/stolen. Secondly, we delegate a part of the computational load of the RAC to the server to balance the load between RAC and server. Thirdly, we introduce the location information of the user's device as another factor without using the GPS service of the mobile device. It helps to authenticate a user with a single sign-on to receive several related services without entering his user ID, password and biometric data again and again. Our scheme uses elliptic curve-based cryptography (ECC) to achieve a robust system with less memory consumption. We have analysed our authentication scheme from several online security threats and verified it to be safe using the Scyther Tool.